Dietary fiber source from pineapple by-product - Suleiman, Norhidayah (2007)
Dietary fiber is the edible part of plants that are resistant to digestion and absorption in small intestine. Two types which are, soluble dietary fiber (SDF) and insoluble dietary fiber (IDF). Recommended to take enough quantities of dietary fiber, for adults 26 to 35 g per day and children 15 to 20 g per day. A lot of benefit by taking dietary fiber such as the health of the digestive system. Previous studies, use cereals and wheat as a source for dietary fiber.